Pentingnya Media Pembelajaran untuk Meningkatkan Minat Belajar di SDN 1 Pasirbatang - Nabila Bilqis; Sunanih Sunanih; Dea Jayanti; Obi Robiyalloh; Fachmi Muzzammil; Anggi Deviyani; Mutiara Harkit Kamilatul Pua’dah; Siti Hazar Rimadani; Tiana Salsabila Agustin; Erni Pitriani; Lia Amelia; Rizky Nurul Meilani; Karlina Delia (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to explore the importance of learning media in increasing students' interest and motivation to learn at SDN Pasirbatang. The method used is descriptive qualitative with semi-structured interviews as the main instrument. The results show that varied, creative, and innovative learning media, such as videos, interactive apps, and other aids, can significantly increase students' interest and motivation to learn. Teachers at SDN Pasirbatang implement technology-based learning strategies and methods such as Problem-Based Learning (PBL) and Cooperative Learning to create an interesting and relevant learning atmosphere. However, limited facilities, technology constraints and senior teachers' lack of skills in using technology are the main challenges. Solutions implemented include individualized approaches, learning media innovation, and student empowerment in media making. Based on the questionnaire results, 82% of students supported the use of learning media, showing the effectiveness of visual and interactive media in improving students' understanding and participation. This research confirms the importance of the role of teachers in utilizing learning media to create more meaningful, effective, and efficient learning, so as to improve the quality of education in primary schools, especially in areas with limited facilities.